2017
DOI: 10.1016/j.ccell.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of PI3Kδ and PI3Kα Induces ABC-DLBCL Regression by Blocking BCR-Dependent and -Independent Activation of NF-κB and AKT

Abstract: Compared with follicular lymphoma, high PI3Kα expression was more prevalent in diffuse large B cell lymphoma (DLBCL), although both tumor types expressed substantial PI3Kδ. Simultaneous inhibition of PI3Kα and PI3Kδ dramatically enhanced the anti-tumor profile in ABC-DLBCL models compared with selective inhibition of PI3Kδ, PI3Kα, or BTK. The anti-tumor activity was associated with suppression of p-AKT and a mechanism of blocking nuclear factor-κB activation driven by CD79, CARD11, TNFAIP3, or MYD88. Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 38 publications
(51 reference statements)
11
110
0
Order By: Relevance
“…In particular, the cell lines derived from MCL and ABC DLBCL presented reduction of p‐AKT and increased cytotoxicity. The benefit of the combination observed in our lymphoma models is in agreement with that observed in CLL models using the same compounds (Niemann et al , ), and also supported by data obtained using different BTK and PI3K inhibitors (Mathews Griner et al , ; Paul et al , ; Yahiaoui et al , ; Faia et al , ; Schaffer et al , ; Tarantelli et al , ; Tarantelli et al , ). Both sets of data support an on‐going clinical study (NCT02328014), which has shown positive signals of activity, especially in ABC DLBCL (Barr et al , ).…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the cell lines derived from MCL and ABC DLBCL presented reduction of p‐AKT and increased cytotoxicity. The benefit of the combination observed in our lymphoma models is in agreement with that observed in CLL models using the same compounds (Niemann et al , ), and also supported by data obtained using different BTK and PI3K inhibitors (Mathews Griner et al , ; Paul et al , ; Yahiaoui et al , ; Faia et al , ; Schaffer et al , ; Tarantelli et al , ; Tarantelli et al , ). Both sets of data support an on‐going clinical study (NCT02328014), which has shown positive signals of activity, especially in ABC DLBCL (Barr et al , ).…”
Section: Discussionsupporting
confidence: 90%
“…Direct measurement of BTK occupancy in CSF, if technically feasible, might provide further insight into this important question. Combination therapy of ibrutinib with inhibitors of p110α/p110δ PI3K or mTOR, which are in advanced stages of clinical testing, may offer a strategy to augment the depth and duration of ibrutinib responses in CD79B -mutant PCNSL and perhaps other DLBCL subgroups (46). Further studies are needed to evaluate if second generation BTK inhibitors with different pharmacokinetic properties and kinase selectivity might augment the remarkable clinical activity of ibrutinib in CNS lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Combination strategies will be critical for better management of PDAC as well as other tumors. In diffuse large B-cell lymphoma, activation of AKT and BTK signaling followed monotherapy treatment with BTK inhibitor ibrutinib and PI3Kα/δ inhibitor copanlisib led to striking improvement in efficacy (14). Cross-resistance to BRAF and MEK inhibitors in melanoma can be overcome with PI3K pathway targeting (15).…”
Section: Introductionmentioning
confidence: 99%